Desire for Trans Ancestors: An Affective Reading of Jordy Rosenberg’s Confessions of the Fox - Zender, Ivo (SQS – Suomen Queer-tutkimuksen Seuran lehti, 2023)
In this article, the relationship between the affective histories of queer and trans activism and the reading and writing of contemporary fictional trans literature is explored. The focus lies on the analysis of Jordy Rosenberg’s (2018) Confessions of the Fox, which allows for an investigation into how trans histories can be written and read. The article emphasizes the intricate interplay between literature and history, specifically examining the tensions and pleasures that arise from balancing authenticity and fictionality. Additionally, the role of literature as a medium for expressing emotions and inspiring activism is considered. Confessions of the Fox tells the story of a fictional transmasculine literary scholar who discovers a mysterious manuscript that reveals the trans identity of 18th century London’s infamous thief and jailbreaker Jack Sheppard. The narrative of Confessions of the Fox establishes an analogy between human bodies and written texts, specifically referring to the trans body. In this article, I argue that the narrative itself approaches the body and the manuscript through the affect of desire. Drawing on the concept of textual desire, as found in Roland Barthes' (1975) The Pleasure of the Text and in the work of Eve Kosofsky Sedgwick (1985), the article analyzes the relationship between text and readership to trace pleasurable and ethical encounters with otherness. Overall, the article puts forward the idea to consider reading practices as a tool through which we can investigate the significance and ramifications of queer and trans histories and activism. Keywords: trans literature, historiographic metafiction, Confessions of the Fox, textual desire, queer reading, trans reading, authenticity, trans literacy